PENINGKATAN PERAN KADER DASA WISMA DALAM PENCEGAHAN RISIKO PTM (PENYAKIT TIDAK MENULAR) DI KECAMATAN DAWAN - V.M ENDANG S.P RAHAYU; N.L.K SULISNADEWI; I WAYAN SUARDANA; Putu Susy Natha Astini; I Ketut Labir (Jurnal Gema Keperawatan, 2019)
Non-communicable diseases  are cases that have increased so far. One effort that can be done to reduce the risk factors and impacts of Non-communicable diseases is to activate Dasawisma cadres. Dasawisma cadres are a form of community participation in helping to control the factors related to sustainability and sustainability. The purpose of this study is to study the evolution of groups in increasing the role of dasawisma cadres in doing opposing Non-communicable diseases. This study used a quasi-experimental design using the pretest-posttest control group design. The number of samples is 80 cadres which are divided into 2 groups and technical samples are taken by Multistage Random Sampling technique. The intervention group was given education about Non-communicable diseases refusal and modules, while the control group only participated in the Posbindu activity and provided the module at the end of the activity. Data analysis using t-test, Mann-Whitney test, and Wilcoxon signature test. The results showed that there was a difference in knowledge = 0.004 motivation = 0,000 and role = 0,000 between intervention groups with control in Non-communicable diseases competition (p-value α = 0.05). Related to the cadre training carried out sustainable knowledge, motivation, and the role of cadres in the Non-communicable diseases struggle can continue to be maintained and improved.